Severe Acute Hepatitis B in HBV-Vaccinated Partner of a Patient with Multiple Myeloma Treated with Cyclophosphamide, Bortezomib, and Dexamethasone and Autologous Stem Cell Transplant - Majed M. Almaghrabi; Kyle J. Fortinsky; David Wong (Case Reports in Hepatology)
Hepatitis B reactivation can occur with various forms of immunosuppression. Cyclophosphamide, Bortezomib, and Dexamethasone (CYBOR-D) chemotherapy is commonly used for the treatment of multiple myeloma and has not been noted in guidelines to be causative in HBV reactivation. Indeed, current guidelines do not recommend providing antiviral prophylaxis to patients with prior HBV infection. We present a case of HBV reactivation as a result of CYBOR-D and autologous stem cell transplant which is complicated by the patient’s partner who developed acute hepatitis B. Our case highlights the need to review the role of antiviral prophylaxis for patients undergoing treatment of multiple myeloma and also the role of ensuring immunity for close contacts of these patients who may also be at risk.